INCORPORATING CONSTRUCTIVISTS LEARNING ENVIRONMENT WITH ROLE PLAYING ELEMENTS INTO 3D ANIMATION CLASSROOMS (Proceeding of the International Conference on Arts and Humanities, 2018)
The teacher-centered learning is one of the most common traditional teaching method, which has existed throughout every level in education system world-wide. This teaching practice had been keeping in line until now, and have been progressively enhanced by various teaching and learning technologies like the internet and learning management systems. However, how well or keen can the students learn from these teacher-centered learning, despite with the aid of learning and teaching technologies that are being granted to them? Regular university practical-based classes, like 3D animation, are mostly handled with the teacher-centered approach, especially during tutorial sessions with the students. Not more than half of the students might be able to retain what they absorb, while the remaining students suffer short-term memory retention. Constructivist teaching and learning approach is one of the learning theories that engages students to actively construct their knowledge, rather than receiving knowledge in a passive state. This study will focus on the implementation of a Constructivist Learning Environment (CLE) for 3D animation classrooms in UCSI University, Malaysia, with a suggested guide and framework. Rather than having a common CLE for the students to engage in, the learning environment itself is enhanced with Role Playing elements, to make it more interactively engaging, fun and interesting for the students to participate.
Keywords: Constructivist learning; Gamification; Problem-based learning; 3D Animation